Assessing the Validity of the Self-Appraisal Questionnaire in Differentiating High-Risk and Violent Female Offenders. (September 2014) - Kubiak, Sheryl Pimlott; Kim, Woo Jong; Bybee, Deborah; Eshelman, Lee
The Self-Appraisal Questionnaire (SAQ) holds promise as a self-report measure that predicts the risk of recidivism and assesses treatment needs for incarcerated populations. However, its validity has been questioned for use with females. Using a random sample of 543 incarcerated women, we assessed the validity of the SAQ by examining differences in scale scores and Receiver Operating Characteristic curves using multiple measures of violent behavior among women. Self-reported violence, versus a violent conviction, was a strong predictor of SAQ scores, but many of those in the most violent group did not meet the published cut scores that indicate treatment need, suggesting the need for adjusting these thresholds for women.